Pregnancy Outcomes in Men and Women Treated With Teriflunomide. A Population-Based Nationwide Danish Register Study - Andersen, Johanna Balslev; Moberg, Julie Yoon; Spelman, Tim; Magyari, Melinda (Frontiers in Immunology, 2018)
Background: The majority of persons diagnosed with multiple sclerosis (MS) experience their first MS symptoms in the reproductive age. Teriflunomide (TFL, Aubaggio), was first released in Denmark for relapsing-remitting MS in December 2013. TFL treatment is contraindicated in women of childbearing potential who are not using reliable contraception. TFL can be transmitted via semen and a low risk of male-mediated embryo-foetal toxicity is described. Objective: To report pregnancy outcomes of TFL-treated women and partners to TFL-treated men: gestation week <week 37, abortions and congenital malformations, caesarean section, live born and stillborn, birth weight and Apgar score. Methods: Prospective cohort study comparing pregnancy outcomes of TFL-treated men and women, matched on age at conception, 1:4 with controls from the general population. Data on TFL-treated patients treated 1st of January 2014 to 31st of December 2016 for at least 30 consecutive days prior to conception, and with conception occurring latest two years after treatment discontinuation were extracted from The Danish Multiple Sclerosis Registry and merged with several national reproductive registries. Logistic regression was used to analyse the association between TFL exposure and any adverse event. Results: A total of 31 pregnancies were recorded, 13 women and 18 of partners to a TFL-treated man. All 18 partners of TFL-treated men completed their pregnancies: livebirth (18), gestation time >37 weeks (17), gestation time 33-36 weeks (1), normal birth weight (18), spontaneous and elective abortion (0), congenital malformation (plagiocephali) (1), normal delivery (14), induced delivery (2), caesarean section (2), Apgar score ≥7 (18). Among the 13 pregnancies in women exposed to TFL: elective abortion (11), spontaneous abortion (0), livebirth (2), gestation time >37 weeks (2), normal birth weight (2), congenital malformations (0), normal delivery (1), induced delivery (1), Apgar score ≥7 (2). The TFL group was associated with a 22% reduction in the odds of any adverse event relative to controls, although this association was not significant (OR 0.78; 95% CI 0.16-3.72, p=0.753). Conclusion: Pregnancy outcomes were consistent with those of the general population. The malformation reported of the partner to a TFL-treated man is comparable to the rate of plagiocephaly reported in Denmark.